2020
DOI: 10.1364/prj.388988
|View full text |Cite
|
Sign up to set email alerts
|

Build-up dynamics in bidirectional soliton fiber lasers

Abstract: Bidirectional ultrafast fiber lasers present an attractive solution, enabling the generation of two mutually coherent ultrashort pulse trains in a simple and turnkey system. Still, the lack of a comprehensive numerical model describing steady-state bidirectional generation, and even less ultrafast soliton breakdowns and collisions, is obstructing the achievement of the performance compared with unidirectional lasers. In this paper, we have experimentally investigated real-time build-up dynamics of counter-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Throughout the entire dynamics and stable propagation, except for central wavelength shift, counterpropagating pulses have had identical repetition rates. In contrast, in our previous work 32 , both pulses had a slight mismatch in repetition rates. Although recorded several dozens of switch-on dynamics demonstrate similar features mentioned above, there has been no preferred sequence of events or single pathway to stable mode-locking generation.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Throughout the entire dynamics and stable propagation, except for central wavelength shift, counterpropagating pulses have had identical repetition rates. In contrast, in our previous work 32 , both pulses had a slight mismatch in repetition rates. Although recorded several dozens of switch-on dynamics demonstrate similar features mentioned above, there has been no preferred sequence of events or single pathway to stable mode-locking generation.…”
mentioning
confidence: 57%
“…When pulses undergo through simpler build-up dynamics shown in ref. 32 no unsynchronised resonant DWs were observed. The results presented here indicate that unsynchronised resonant DWs are dependent on the initial conditions of pulse formation.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Some critical phenomena are also observed, including transient complex spectrum broadening and frequency-shift interaction of SPs and picosecond pulses. More recently, Kudelin et al experimentally demonstrated that bidirectional soliton fiber laser experience independent buildup dynamics from modulation instability, undergoing breathing dynamics and diverging sub-ordinate pulse structures formation and annihilation [234]. In the same way, the similar behaviors dissipative soliton in a net-normal-dispersion bidirectional ultrafast fiber laser were also observed by Luo et al [235].…”
Section: Entire Formation Dynamics Of Solitons 421 Buildup Dynamicsmentioning
confidence: 60%
“…In the current presentation, real-time build-up dynamics of counter-propagating solitons in ultrafast ring Er-doped fibre laser, recorded via the dispersive Fourier transform methodology, will be discussed [9]. Even though the counter-propagating pulses experience independent build-up dynamics from modulation instability, undergoing breathing dynamics, diverging sub-ordinate pulse structures formation and annihilation, and Q-swtuch instabilities, etc.…”
mentioning
confidence: 99%